LATERAL FORCE PERCEIVED BY CONCRETE IN THE INCLINED SECTION OF REINFORCED CONCRETE ELEMENTS - Y. V. Krasnoshchekov (Вестник СибАДИ)
Introduction. The article presents results of the empirical dependence analysis of transverse force in the inclined section of reinforced concrete elements.Materials and methods. Long-term application of such dependence at the reinforced concrete design demonstrates high parameters’ reliability. Thus, analyzed information could be used in innovated calculation model, which includes joint action of cross forces and bending moments.Results. The analysis of empirical dependence by the design standards seems to obtain information about the limit value of shear stresses in the compressed zone of inclined concrete and their interrelations with normal stresses. The results of the analysis were tested on computer models of the beam using finite elements. It does, however, assume that the shear resistance is specifically related to compression resistance by means of a special coefficient, which could be determined by computer simulation.Discussion and conclusions. The calculated values of the inclined section of reinforced concrete elements in the transverse bending could be specified by experimental or computer modeling.